Odpowiedzi

2010-01-08T16:44:29+01:00
(x-y) 5x 19
3------- + 0,25= ---- - y + ----
4 2 5 /*20

3x – 1 y + 9
-------- - ------- = (-2x)
5 2 /*10

15(x-y) + 5= 10 × 5x - 20y + 4 × 19
2(3x-1) - 5(y+9) = -20x

15x - 15y + 5 = 50x + 76
6x - 2 -5y - 45= -20

15x-50x=76-5+15y
6x-5y= -20 + 45 + 2

-35x = 71 + 15
6x- 5y= 27

-35x= 86 /: (-35)
6x-5y=27

86
x= - -------
35

-86
6 × ---- - 5y = 27
35

516
- ------ - 5y = 27
35
516
- 5y = 27 + ------
35

26
- 5y= 27 + 14 -----
35

26
-5y= 31 -------
35

1111
-5y= ------- /*(-1/5)
35

1111 61
y= - ------- = - 6 ------
175 175

86 16
x= - ------- = - 2 -----
35 35